A STUDY OF WOMEN’S LANGUAGE VARIETIES IN FRENCH MOVIE - HARDINI, Tri Indri; DARMAWANGSA, Dante; NADA, Annisa Ghaida (FRANCISOLA, 2017)
RÉSUMÉ. Cette étude traite les variétés de langues féminines dans un film français. Les objets de cette étude sont les énoncés de personnages féminins, à la fois dans le dialogue et le monologue. Cette étude vise à décrire les types de variétés de langue de la femme contenues dans le film, et les variants de la langue des femmes les plus fréquentes. La recherche a été menée en utilisant une approche qualitative où les données sont recueillies en utilisant des techniques d'observation et de prise de notes. Les données obtenues ont été tabulées en cartes de données afin de faciliter le processus d'analyse. Les résultats montrent qu'il y a 10 types de variétés de langue féminine apparues, à savoir lexical hedges or fillers, tag question, rising intonation on declaratives, ‘empty’ adjective, intensifiers, ‘hypercorrect’ grammar, super-polite forms, emphatic stress, gossip, and feedback. La variété la plus fréquente est intonation on declarative variety (50.9%) et celle la moins fréquente est lexical hedge or fillers (0.9%). Ce résultat devrait contribuer positivement au développement de l'étude sociolinguistique, en particulier sur l'étude de la variété des langues chez l'homme et chez la femme.Mots-clés : film français, personnages féminins, sociolinguistique, variétés de langues féminines.  ABSTRACT. This study investigates women’s language varieties in a French movie. The objects of this study are the utterances of woman characters, both in dialogue and monologue. This study aims to describe the types of woman language varieties contained in the movie, and the most frequent variants of the woman language. The study was conducted using qualitative approach where the data gathered using observation and note-taking techniques. The obtained data were tabulated into data cards to facilitate the analysis process. The results show that there are 10 types of woman language varieties appeared, namely lexical hedges or fillers, tag question, rising intonation on declaratives, ‘empty’ adjective, intensifiers, ‘hypercorrect’ grammar, super-polite forms, emphatic stress, gossip, and feedback. The most appeared variety is rising intonation on declarative variety (50.9%) and the least appeared variety is lexical hedge or fillers (0.9%). This finding is expected to contribute positively in the development of sociolinguistics study, especially on the study of man and woman language variety.Keywords: French movie, sociolinguistic, women’s language varieties, woman characters.